Distinguishing tautomerism in the crystal structure of (Z)‐N‐(5‐ethyl‐2, 3‐dihydro‐1, 3, 4‐thiadiazol‐2‐ylidene)‐4‐methylbenzenesulfonamide using DFT‐D calculations and 13C solid‐state NMR. Issue 8 (21st July 2014) - Li, Xiaozhou; Bond, Andrew D.; Johansson, Kristoffer E.; Van de Streek, Jacco
<x xml:space="preserve">Abstract</x> The crystal structure of the title compound, C11H13N3O2S2, has been determined previously on the basis of refinement against laboratory powder X‐ray diffraction (PXRD) data, supported by comparison of measured and calculated 13C solid‐state NMR spectra [Hangan et al. (2010). Acta Cryst. B66, 615–621]. The molecule is tautomeric, and was reported as an amine tautomer [systematic name: N‐(5‐ethyl‐1, 3, 4‐thiadiazol‐2‐yl)‐p‐toluenesulfonamide], rather than the correct imine tautomer. The protonation site on the molecule's 1, 3, 4‐thiadiazole ring is indicated by the intermolecular contacts in the crystal structure: N—H...O hydrogen bonds are established at the correct site, while the alternative protonation site does not establish any notable intermolecular interactions. The two tautomers provide essentially identical Rietveld fits to laboratory PXRD data, and therefore they cannot be directly distinguished in this way. However, the correct tautomer can be distinguished from the incorrect one by previously reported quantitative criteria based on the extent of structural distortion on optimization of the crystal structure using dispersion‐corrected density functional theory (DFT‐D) calculations. Calculation of the 13C SS‐NMR spectrum based on the correct imine tautomer also provides considerably better agreement with the measured 13C SS‐NMR spectrum.